Fortune Telling and American Religious Freedom. Issue 2 (18th June 2018) - McCrary, Charles
Abstract: In the late nineteenth and early twentieth centuries, a number of people who were arrested for pretending telling fortunes appealed their convictions on religious freedom grounds. These accused fortune tellers, mostly white spiritualist women, were arrested for violating state statutes across the United States, from New York to Georgia to Oklahoma to Washington. Though each defendant lost her case, their arguments showcase previously understudied early twentieth-century attempts by relatively disempowered actors to expand the scope of religious freedom. One law professor, named Blewett Lee, wrote a series of articles in the 1920s in which he considered these cases and their implications, identifying central problems and advancing prescient arguments about religious freedom. This article thinks with Lee and the accused fortune tellers to highlight two key aspects of secularism and American religious freedom. First, it uncovers the epistemological assumptions embedded into jurisprudence and legislation around "fortune telling." Many of the statutes, which were based on English vagrancy laws, applied to "persons pretending to tell fortunes." The term "pretending" raised questions about what the law presumed to be true and whether secular states could adjudicate religious veracity. Second, this article argues that secularism is regulatory and that scholars should connect religious freedom to histories of policing, licensure, and other forms of regulation. These two aspects, one primarily conceptual and the other practical and procedure, work together to delineate the parameters of American religious freedom, as secular state agents both define "religious belief" and regulate believers.